Theoretical study of the hydration effects on alkylamine and alkanolamine clusters and the atmospheric implication. (March 2020) - Ge, Pu; Luo, Gen; Huang, Wei; Xie, Hongbin; Chen, Jingwen; Luo, Yi
Abstract: Amines are important atmospheric nucleation precursors in polluted areas. However, specific roles of various amines in enhancing the stability of pre-nucleation clusters are poorly understood. Herein, different roles of trimethylamine (TMA) and monoethanolamine (MEA) in the formation of sulfuric acid (SA)-based pre-nucleation clusters were investigated. The hydration effects of up to four water (W) molecules on the interaction of the acid-base pairs of (TMA)(SA) and (MEA)(SA) were computationally investigated at the M06–2X/6–311++G (3df, 3pd) level of theory. Results show that the formation thermodynamics of key intermediate clusters are different with amines. Besides, MEA-enhanced formation of pre-nucleation clusters plays an important role in environments with high humidity while TMA may be the dominant nucleation precursors in dry conditions. The concentration of dominant MEA-containing pre-nucleation cluster is at least three orders of magnitude higher than that of TMA and dimethylamine near emission sources at conditions of T = 298.15 K and RH = 60%, indicating that alkanolamine may play an important role in atmospheric nucleation. Furthermore, the hydration of MEA is easier than that of alkylamines. Our results put forward the need to distinguish the performance of different types of amine under specific conditions to better model the new particle formation events in highly polluted areas. Besides, this study indicates that alkanolamines such as MEA are important participator in new particle formation. Graphical abstract: Image 1 Highlights: High humidity promotes monoethanolamine-enhanced pre-nucleation cluster formation. Monoethanolamine is an important participator in initial steps of nucleation. Hydration of monoethanolamine is easier than that of alkylamines.